2015
DOI: 10.1590/s0102-865020150060000010
|View full text |Cite
|
Sign up to set email alerts
|

Post-hemorrhagic shock mesenteric lymph is an important contributor to cardiac dysfunction following hemorrhagic shock

Abstract: PURPOSE:To evaluate whether post-hemorrhagic shock mesenteric lymph (PSML) is involved in cardiac dysfunction induced by hemorrhagic shock. METHODS:The hemorrhagic shock model (40±2 mmHg, 3h) was established in rats of the shock and shock+drainage groups; and PSML drainage was performed from hypotension 1-3h in the shock+drainage rats. Then, the isolated hearts were obtained from the rats for the examination of cardiac function with Langendorff system. Subsequently, the isolated hearts were obtained from norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The return of post-hemorrhagic shock mesenteric lymph (PHSML) is a key reason of multiple organ dysfunction caused by hemorrhagic shock. Therefore, mesenteric lymph drainage or mesenteric lymph duct ligation improve the multiple organ functions and reduce the tissue injury following hemorrhagic shock, such as lung, heart and kidney 4 10 . Recently, the role of PHSML in the pathogenesis of hemorrhagic shock has attracted increasing attention 11 – 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The return of post-hemorrhagic shock mesenteric lymph (PHSML) is a key reason of multiple organ dysfunction caused by hemorrhagic shock. Therefore, mesenteric lymph drainage or mesenteric lymph duct ligation improve the multiple organ functions and reduce the tissue injury following hemorrhagic shock, such as lung, heart and kidney 4 10 . Recently, the role of PHSML in the pathogenesis of hemorrhagic shock has attracted increasing attention 11 – 13 .…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] CaM is a key factor for the regulation of myocardial cell contraction, and insufficient CaM is one of the main mechanisms responsible for myocardial dysfunction and calcium desensitization in cardiomyocytes. 20 , 21 Since PHSML return is a primary cause for hemorrhagic shock-induced myocardial systolic dysfunction, [9][10][11] the present study firstly observed the effects of MLDL and PHSML drainage on CaM expression in papillary muscles. We found that hemorrhagic shock decreased the expression of CaM in papillary muscles, which was reversed by blockade of PHSML return.…”
Section: Discussionmentioning
confidence: 85%
“…By contrast, administration of PHSML to healthy rats causes decreases in left ventricular systolic pressure and the ±dP/dtmax of isolated heart pump functions. 9 Moreover, MLDL enhances myocardial contraction function and sensitivity of the heart to gradient calcium ion 10 , while intravenous injection of PHSML into immature rats causes myocardial contraction dysfunction. 11 Therefore, PHSML return is a critical factor to regulate the pump function of heart after hemorrhagic shock.…”
Section: Introductionmentioning
confidence: 99%
“…an initial dose dependent inotropic effect immediately after exposure, which was followed by progressive loss of contractile function (31). A recent study revealed a reduction in cardiac contractile dysfunction following H-S in animals subject to mesenteric lymph drainage (65). The lymph studied was sterile and contained similar levels of cytokines when compared to lymph from control animals, thereby suggesting a role for ALARMIN and DAMP type molecules in the process (31,32).…”
Section: Hearts and Cardiomyocytes Exposed To Lymph From T-h Exposed Animals Demonstratedmentioning
confidence: 90%